Empowerment edukatif Guru PAUD dalam pembuatan Alat Permainan Edukasi ramah anak inklusi berorientasi SALINGTEMAS - Negara, Tirta Dimas Wahyu; Fauziah, Hanin Niswatul (WISDOM: Jurnal Pendidikan Anak Usia Dini, 2022)
This article was written based on the results of training and mentoring activities for PAUD teachers who are members of the IGRA Association (Ikatan Guru Raudhatul Athfal) Ponorogo. Training and mentoring activities are useful for training teachers' abilities in making APE (Educational Game Tools) for inclusive children by prioritizing the Salingtemas approach (science, environment, technology, society). The purpose of this activity is to realize the ideals of quality education for all through inclusive schools. The method used in this activity is ABCD, which begins with mapping IGRA Ponorogo assets. Based on all the stages that have been passed, it can be said that this activity has succeeded in creating APE in accordance with the criteria for inclusive schools. The next conclusion is that IGRA Ponorogo has never received similar training, so that when the activity was carried out, the enthusiasm of the trainees appeared. In the end, it can be said that this activity has succeeded in increasing the knowledge, skills and attitudes of teachers in dealing with children with special needs.